THE ROLE OF POLYSEMANTIC WORDS IN SPEECH - Bozorov Behruz Ilhom oʻgʻli (Bright Mind Publishing, 2025)
This scientific article presents ideas and observations about the use of polysemantic words in speech.
Keywords: Language, morphology, polysemantic, speech, style, society, principle, linguistics.